All these poses, such beautiful Poses: articulations of queer masculinity in the music of Rufus Wainwright - Jones, Matthew J. (Université de Géorgie, 2008)
Singer-composer Rufus Wainwright uses specific musical gestures to reference historical archetypes of urban, gay masculinity on his 2002 album Poses. The cumulative result of his penchant for pastiche, eschewal of traditional musical boundaries, and self-described hedonism, Poses represents Wainwright’s direct engagement with the politics of identity and challenges dominant constructions of (homo)sexuality and masculinity in popular music. Drawing from a vast lexicon of musical styles, he assembles an idiosyncratic persona, ignoring several decades of pop with an “utter lack of machismo [and] a freedom that comes to outsiders disinterested in meeting the requirements of the dreary status quo.”1 Though analysis of musical and lyrical characteristics of Poses, I establish a dialectic between Wainwright’s musical persona and four historical modes of urban gay masculinity: the 19th Century English Dandy, the French flaneur, the 20th Century gay bohemian, and the “Clone.” In doing so, I introduce Wainwright as a reinvigorating force, resuscitating the subversive potential of radical gay sexuality as a 21st Century model for imagining gay male subjectivity.

Sobre meninos e homens Por uma leitura edipiana: Rufus Wainwright e a canção Dinner at Eight [Des garçons et des hommes: Rufus Wainwright et la chanson "Dinner at Eight"] - Júnio, José Mariano Tavares (Cadernos do LINCC, 2008)
O artigo reflete sobre a obra do compositor novaiorquino Rufus Wainwright iconsiderando as suas influências no sentido de explicar, ao menos em parte, a originalidade melódica e harmônica presente na arquitetura de suas canções, a grandiloqüência dramática dos arranjos, e a complexidade de sua persona artística, opondo, a uma forte teatralidade camp, a melancolia trágica, cortante, do solitário e outsider.

L'identité culturelle dans « Montréal », d'Ariane Moffatt : une analyse musicale sémiologique - Laurier-Cromp, Mélanie (Université McGill, 2008)
La chanson « Montréal », d'Ariane Moffatt, a remporté un vif succès durant l'été 2006. Ce mémoire examine les causes de cette popularité. Après une revue des diverses méthodes existantes en recherche en musique populaire, trois types d'analyse se succèdent. En premier lieu, l'étude présentée ici décrit la chanson de manière théorique; on y observe le fonctionnement de la voix, de la mélodie, de la métrique, de la basse, des phrases, de la tonalité, des accords et des instruments utilises, images par une transcription précise de l'enregistrement de la chanson. Puis, le présent travail étudie les codes musicaux qui se retrouvent dans «Montréal». Dans cette deuxième section, le message musical du morceau est analysé, en tenant compte du contexte socioculturel de l'été 2006, de l'histoire nationale et musicale qui a précédé la sortie de cette pièce et des paroles de la chanson. Finalement, cette étude investigue la composante identitaire de «Montréal» en examinant les croyances nationalistes des Québécois, la place de la chanson dans l'imaginaire collectif de ce peuple, et la tradition musicale populaire de la province.

Rufus Wainwright [entrevista]: Geni i figura - Broc, David (Benzina: Revista d'excepcions culturals, 2007)

Rufus Wainwright. Interview by Paul Zollo - Zollo, Paul (Song: the World’s Best Songwriters on Creating the Music that Moves Us, 2007)
Song is an enthralling compilation of songwriting wisdom from 100 of the biggest names in music. From country to rock to folk to alternative, this genre-spanning collection of interviews captures the anecdotes, history, and wisdom of the best songwriters around - in their words. An entertaining read as well as an indispensable guide to the art and craft of songwriting, Song is a must-have resource for the aspiring, amateur, or professional musician. Inside, you'll find entertaining and enlightening interviews from great songwriters such as Smokey Robinson, Willie Nelson, Jewel, Kenny Chesney, Cat Stevens, Jack Johnson, Sheryl Crow, John Legend, John Mellencamp, Ray Charles, Clint Black, Rob Thomas, Dolly Parton, Rufus Wainwright, Bob McDill, Lyle Lovett, Keith Urban, Beck, M. Ward, Lou Reed, Roger Miller, Grant-Lee Phillips, and John Denver.

Michel Louvain : héritage, circonstances et convergences - Savoie, Chantal (Groove. Enquête sur les phénomènes musicaux contemporains, 2006)
En juin 2003 décédait tragiquement Roger Chamberland. Professeur titulaire à l’Université Laval, directeur du Département des littératures, cet homme du présent multipliait compétences et engagements dans une urgence aussi fervente que généreuse. Ses intérêts de recherche portaient sur des objets à la croisée des mouvements littéraires, artistiques et technologiques de son temps : formes variées de la culture populaire, expressions musicales contemporaines, esthétiques nouvelles étaient pour lui autant de champs d’investigation dignes de l’attention du chercheur d’aujourd’hui. Codirigé par Patrick Roy et Serge Lacasse, le présent ouvrage porte trace de cette enquête sur notre post-modernité. Il rend hommage au professeur, au chercheur qu’était Roger Chamberland. Ceux qui ont côtoyé cet homme d’exception, ses étudiants, ses collègues, ses amis, savent qu’il était infiniment plus que cela.

Rufus Wainwright - De Curtis, Anthony (In Other Words: Artists Talk About Life and Work, 2005)